Pengaruh Model Pembelajaran CTL (Contextual Teaching And Learning) dalam Meningkatkan Hasil Belajar - Putri Vina Sefaverdiana (IKIP Budi Utomo Malang, 2022)
The main problem in learning is understanding the material in the form of a theory that is difficult to learn. Memorization will also be difficult to implement to understanding. So that using the Contextual Teaching and Learning (CTL) learning model is the right choice, with the aim that students are able to understand the material by relating the material to everyday life. This study uses experimental methods, the static group pretest and posttest designs. Collecting data using observation and tests. The data obtained shows that Contextual Teaching and Learning (CTL) learning has an effect on learning outcomes because students are very active in learning. Students are enthusiastic in discussions and easily express opinions because it is related to what they have experienced.